Sex-specific differences in bone mineral density loss after sleeve gastrectomy - Yang, Di; Ye, Yafen; Tu, Yinfang; Xu, Rongrong; Xiao, Yunfeng; Zhang, Hongwei; Liu, Weijie; Zhang, Pin; Yu, Haoyong; Bao, Yuqian; Han, Junfeng (Frontiers in Medicine, 2022)
Background: Sleeve gastrectomy is an effective bariatric procedure; however, sleeve gastrectomy-related adverse skeletal outcomes have been increasingly reported. High levels of sex hormone-binding globulin (SHBG) have been documented to be a risk factor of bone mineral density (BMD) loss with different effects observed between sexes. The aim of this study was to identify sex-specific changes in BMD following sleeve gastrectomy and to evaluate the role of SHBG in this process. Methods: This retrospective study included 19 middle-aged men and 30 non-menopausal women with obesity who underwent sleeve gastrectomy in China. Anthropometrics, bone turnover markers, calciotropic hormones, BMD, SHBG, and gonadal steroids were measured preoperatively and at 6 and 12 months postoperatively. Longitudinal changes in BMD, bone turnover markers and SHBG were compared between sexes by linear mixed models. Multiple stepwise regression analysis was used to identify the independent predictors of BMD loss at the investigated bone sites. Results: Over the 12-month study period, total hip and femoral neck BMD decreased, while lumbar spine BMD remained largely unchanged in both sexes. Linear mixed models revealed significant sex × time interaction effects in total hip BMD and SHBG, showing that men had a significantly greater reduction in total hip BMD and less increase in SHBG after sleeve gastrectomy than women. In the multivariate model, SHBG was significantly associated with total hip BMD loss in men (adjusted β=-0.533, P=0.019) but not women while total estrogen was significantly associated with total hip BMD loss in women (adjusted β=0.508, P=0.01) but not men. Conclusion: Significant sex-specific BMD changes were observed after sleeve gastrectomy in the current study. Sleeve gastrectomy-related increase in SHBG may be a specific risk factor for total hip BMD loss in men. Our results indicate that sex-specific screening may be warranted to facilitate personalized postoperative bone care in this population.